Implementasi Program Pembuatan Akta Kematian di Desa Prikuku Kecamatan Prikuku Kabupaten Pacitan dari Kacamata Komunikasi, Komitmen, Sumber Daya dan Struktur Birokrasi - Sumarni Sumarni (Pancanaka, 2022)
Indonesia is a constitutional state where all government activities are orderly in all matters including population administration including death certificates. Death Certificates can also function as a tool or a completeness in the management of various kinds of needs such as the processing of new family cards, distribution of inheritance, pensions for civil servants. This research wants to see how much public awareness of the existence of this administration. This research uses descriptive qualitative which is located in Prikuku Village, Pacitan Regency. The program for making death certificates in its implementation process is influenced by 4 factors namely communication, commitment, resources and bureaucratic structure. Research results showing that each factor influences each other, and the implementation of policy making does not require a long time depending on the volume level used, done by the dukcapil. The level of people's desire to take care of this death certificate is still low, the death rate and the rate for processing death certificates are not balanced and this condition can be overcome by communication in the form of outreach carried out by related to raising the public's awareness about making death certificates.